Identification of deregulation in protein expression level of erlotinib-resistant A549 cell lines - Mohd Noh, Noor Khafizah (2015)
Despite modern advancements in surgeries, chemotherapies, and radiotherapies over the past few years, lung cancer still remains a very difficult disease to treat. This has left the death rate from lung cancer victims largely unchanged throughout the past few decades. A key cause for the high mortality rate is the drug resistance that builds up for patients being currently treated with the chemotherapeutic agents. Erlotinib is found to be an effective drug in treating the non-small cell lung cancer (NSCLC). However, development of resistance towards this drug has become one of the major clinical problems. Development of cell resistance is hypothesized to involve in deregulation of protein expression in the cell cycle. Two cell lines namely A549 and A549R (erlotinib-resistant A549) were used to compare and contrast the level of these protein expression in the cell cycle. This will provide supporting information on the development of erlotinib-resistant NSCLC. In this experiment, the optimization of total protein lysate required was conducted to observe differences in protein expression of selected cell cycles payers such as cyclin A, cyclin E, cyclin D, CDK4, CDK6, NF-κB and p-21. The result shows protein expression of cyclin A could be differentiate if the total lysate of 100µg protein were used. Therefore, a better understanding of the characterization and mechanism of resistance to erlotinib in A549R cells is important in the identification of agents that could reverse clinical erlotinib resistance in NSCLC.